Republic of Madagascar : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix analyzes the relationship among prices, income, and money in Madagascar over the period 1982-2004. It finds that a stable long-run relationship for the price level exists, but that the adjustment toward this long-term equilibrium is quite slow. The paper presents an assessment of the real effective exchange rate. It also presents some qualitative competitiveness indicators and examines the performance of exports in Madagascar at an aggregate and product level.